Preference Representation and the Influence of Political Parties in Majoritarian vs. Proportional Systems: An Almost Ideal Empirical Test - David Stadelmann; Marco Portmann; Reiner Eichenberger (Center for Research in Economics, Management and the Arts (CREMA), 2012)
Electoral systems determine the role party affiliations play in political representation. According to conventional expectations, politicians' party affiliations should influence political representation when they are elected by proportional representation. In contrast, majoritarian systems force politicians to converge to the median position of their constituents, and party affiliation should play no or at least a much smaller role. We test these predictions with unique quasi-experimental data within a common party system by matching referenda decisions of constituents with voting behavior of their representatives, who are elected either by a majoritarian system or proportional representation.
Keywords: D7; H7; 330; Constituents' Preferences; Party Influence; Median Voter Model; Political Economy